The clinical outcomes of surgical treatment for chronic ankle instability by anatomical reconstruction of the anterior talofibular ligament with autologous half-bundle peroneal longus tendon: A retrospective study - Luo, Yeqiang; Lin, Shanghui; Kong, Lingchuang; Jin, Yan; Wang, Renkai; Zhang, Ying; Li, Baofeng; Chen, Bei (Frontiers in Surgery, 2022)
The anterior talofibular ligament is the weakest and most vulnerable lateral ligament to be injured, and it can replace anatomical position through anatomical reconstruction. The purpose of this study is to evaluate clinical outcomes after an autologous half-bundle peroneus longus tendon anatomical reconstruction. We conducted a retrospective analysis by enrolling 34 patients [22 male and 12 female, median age 21 (range 19-26) years] with anterior talofibular ligament injury from January 2018 to March 2020. All patients underwent a ligament anatomical reconstruction operation with autologous half-bundle peroneus longus tendon and followed up with an average time of 16.21±3.20(range 12-24) months, with no loss of patients to follow-up during the study period. The American Orthopedic Foot, Ankle Society Score (AOFAS), Visual Analogue Score (VAS), and Anterior Tibiotalar Translation were used to assess the curative effect. All the indexes were compared between the preoperative and at the final follow-up to discover the related statistical differences. The AOFAS score improved significantly from an average preoperative score of 56.91±3.79 to 94.12±2.51 at the final followed-up (p <0.001). Meanwhile, the pre-operation VAS pain score decreased from 5.94±1.32 to 1.71±0.87 (p <0.001). Additionally, the Anterior tibiotalar translation decreased from 16.40±1.85 to 5.20±0.57 mm at the final followed-up (p<0.001). The anterior drawer test was negative for all patients after the operation. Considering the outcomes, we concluded that anatomical reconstruction of the anterior talofibular ligament with autologous half-bundle peroneal longus tendon was a proper and safe procedure for chronic lateral ankle instability, and it had good clinical results and minimal complications.